Challenges in the Design of Prefabricated Single-Family Buildings with Expanded Clay Technology - Selected Architectural and Environmental Aspects - Bradecki, Tomasz; Tofiluk, Anna; Uherek-Bradecka, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The architectural form of buildings is determined by many factors, one of the most important is construction technology. It remains in a close and inseparable relationship with architectural design. Contemporary technologies in construction are constantly subject to improvements, streamlining, changes aimed at increasing all kinds of efficiency (cost, thermal efficiency, labor input, etc.). One of today's widely discussed determinants of changes in the way buildings are designed and constructed is environmental issue. An awareness of environmental degradation and climate change and their consequences prompts the search for increasingly sustainable solutions. This paper summarizes the research on prefabricated solutions and their implementation, especially in single-family residential architecture.
Keywords: climate change mitigation; building energy efficiency; single-family houses; prefabrication; prefab architecture; expanded clay; sustainability by prefabrication; zmiany klimatu; łagodzenie zmian klimatycznych; efektywność energetyczna budynków; domy jednorodzinne; prefabrykaty; keramzyt; trwałość prefabrykatów